Fetomaternal outcome of women with thrombocytopenia in labour - Thakkar, Palak; Desai, Dhwani; Verma, Ragini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study was conducted to study fetomaternal outcome in pregnancy with severity of thrombocytopenia. Methods: It was a prospective observational study of fetomaternal outcome of women with thrombocytopenia admitted in labour room of a tertiary health care center of south Gujarat for 1-year period (April 2021-March 2022) after official approval from ethical committee. 100 consecutive consenting women with thrombocytopenia admitted in labour room of New Civil Hospital Surat were enrolled in this study. Results: Mild thrombocytopenia was noted in 68% of the total cases, moderate thrombocytopenia in 27% and severe thrombocytopenia in 5% of cases. 59 subjects belong to age group of 20-25 years, 56 subjects were multipara, 70 subjects were registered antenatally, 68 subjects were delivered beyond 37 weeks of gestation. 48 subjects underwent LSCS and rest were delivered vaginally. 29 subjects had maternal complication. 95 subjects delivered alive baby of which 14 had NICU admission and 5 subjects had preterm still birth baby. Conclusions: Thrombocytopenia is the second most common haematological finding in pregnancy next to anaemia. Majority of cases generally present at gestational age beyond thirty-seven weeks and belong to category of mild thrombocytopenia. Efforts should be made on improving antenatal registration, screening of maternal thrombocytopenia, early diagnosis and treatment.